2017
DOI: 10.31234/osf.io/2qbmp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent use of animacy and event-knowledge during comprehension: Evidence from event-related potentials

Abstract: In two ERP experiments, we investigated whether readers prioritize animacy over real-world event-knowledge during sentence comprehension. We used the paradigm of Paczynski and Kuperberg (2012), who argued that animacy is prioritized based on the observations that the ‘related anomaly effect’ (reduced N400s for context-related anomalous words compared to unrelated words) does not occur for animacy violations, and that animacy violations but not relatedness violations elicit P600 effects. Participants read passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(123 reference statements)
1
4
0
Order By: Relevance
“…Though both “jacket” and “towel” in (30-a) taken from Metusalem et al ( 2012 ) share few features with the best completion “snowman” and both words are highly atypical given the partial event structure built up preceding the CW in the target sentence, “jacket” elicited a reduced N400 amplitude compared to “towel.” However, this attenuation only occurred when the target sentence was embedded in the wider context given in (30-a) and not when it was used in isolation. A similar argument holds for (30-b) taken from Vega-Mendoza et al ( 2021 ), which is a replication study of Paczynski and Kuperberg ( 2012 ). The authors found the following pattern of N400 amplitude per condition: plausible control (psychiatrist) < animate-related (schizophrenic) < animate-unrelated (guard) < inanimate-related (pill) < inanimate-unrelated (fence).…”
Section: Outline Of a Formalizationsupporting
confidence: 62%
See 1 more Smart Citation
“…Though both “jacket” and “towel” in (30-a) taken from Metusalem et al ( 2012 ) share few features with the best completion “snowman” and both words are highly atypical given the partial event structure built up preceding the CW in the target sentence, “jacket” elicited a reduced N400 amplitude compared to “towel.” However, this attenuation only occurred when the target sentence was embedded in the wider context given in (30-a) and not when it was used in isolation. A similar argument holds for (30-b) taken from Vega-Mendoza et al ( 2021 ), which is a replication study of Paczynski and Kuperberg ( 2012 ). The authors found the following pattern of N400 amplitude per condition: plausible control (psychiatrist) < animate-related (schizophrenic) < animate-unrelated (guard) < inanimate-related (pill) < inanimate-unrelated (fence).…”
Section: Outline Of a Formalizationsupporting
confidence: 62%
“…Second, in the original study Paczynski and Kuperberg ( 2012 ) the authors found (a) an interaction wherein related words elicited smaller N400 amplitudes than unrelated words when these words were animate, but not when they were inanimate and (b) animate-related words like “schizophrenic” did not elicit a reliable N400 effect compared to control words. For a discussion of the differences in the methodological design of the two studies, see Vega-Mendoza et al ( 2021 ).…”
mentioning
confidence: 99%
“…The participants could have strategically paid attention to the possessor words in the second phrase (Dana's) because they cued impending sentence ungrammaticality, and this attention-strategy could have played out differently depending on whether the first phrase also contained a possessor word. This is important because task-relevant words can elicit ERP effects that one would not observe without task (e.g., Baggio, 2012;Roehm et al, 2007;Vega-Mendoza et al, 2017), effects that could reflect evaluation of the materials, decision-making, and possibly response planning (Polich and Kok, 1995). Moreover, task-associated ERPs can be of fairly long duration and spill-over into the time window of the critical word, causing differences to appear early as 0 ms after word onset.…”
Section: What Is the Role Of The Pre-critical Words And The Task?mentioning
confidence: 99%
“…A secondary, explicit task (e.g., acceptability judgments) is sometimes very useful and informative (e.g., to determine whether two groups of participants evaluate sentences equally accurately), and sometimes boosts some of the processes involved in comprehension. However, such a task itself can generate brain responses that distort the effects of interest and induce strategic behaviors that are not representative of the processes that one is trying to explain (Roehm et al, 2007;Vega-Mendoza et al, 2017). Demonstrations of the broader relevance of prediction are most convincing when participants are simply reading or listening to naturalistic materials under the instruction to comprehend the materials to their best ability, or perhaps when they are instructed to answer questions about the content of the stimulus materials that have nothing to do with the manipulation of interest (for further reading, see Willems, 2015).…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Compatible with this idea, sentence-final words following partially matching nouns elicit an N400-like effect compared to the other three conditions. Several studies have reported N400-like negativities for sentence-final words of unexpected or otherwise difficult sentences (Anderson and Holcomb, 2005; Paczynski and Kuperberg, 2012; Nieuwland, 2014; Vega-Mendoza et al, 2018), suggestive of continued sentence comprehension difficulty. Such effects may be more pronounced when participants perform a meta-linguistic judgment task (Nieuwland, 2014; Vega-Mendoza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%